Monocyte-driven IFN and TNF programs orchestrate inflammatory networks in antisynthetase syndrome-associated interstitial lung disease - Fan, Yu; Zhang, Weijin; Su, Miaotong; Zheng, Shaoyu; Lin, Jianqun; Zheng, Kedi; Shen, Fengcai; Zhang, Guohong; Wang, Yukai (Frontiers in Immunology, 2025)
ObjectiveAntisynthetase syndrome-associated interstitial lung disease (ASS-ILD) exhibits clinical heterogeneity and progression, with unclear immunopathogenic mechanisms. This study aimed to define the cell type-specific interferon immune signatures and transcriptional networks underlying ASS-ILD.MethodsSingle-cell RNA sequencing (scRNA-seq) was performed on peripheral blood mononuclear cells (PBMCs) from three treatment-naive ASS-ILD patients and three healthy controls (67,421 cells). A comprehensive analysis was conducted in conjunction with an external cohort, encompassing 126,026 cells. The analytical pipelines included the following: AUCell for interferon-stimulated gene (ISG) activity scoring, Seurat for clustering, Monocle for trajectory inference, and CellChat for cell–cell communication. The inference of transcription factor activity was facilitated using decoupleR software.ResultsMonocyte-specific ISG activity was identified and validated in an integrated cohort of 126,026 cells. Among the six monocyte subsets, mono2 exhibited elevated IFNG expressions and a preferential inflammatory trajectory, marked by upregulated innate and adaptive immune pathways. Cell-cell interaction modeling revealed dysregulated type II interferon (IFN-II) and tumor necrosis factor (TNF) signaling, with mono2, NK, and CD8+ T cells as key signal transmitters. Regulatory network analysis revealed that the transcription factors ETV5, IRF5, IRF7, RORB, RORC, and SMAD1 drive inflammatory and profibrotic signatures via the IL-17, JAK-STAT, and TGF-β pathways.ConclusionsThis study identifies monocytes as central orchestrators of immune dysregulation in ASS-ILD, highlighting IFN/TNF signaling and associated transcriptional regulators as therapeutic targets.